2014
DOI: 10.5539/jas.v6n9p21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment of Sorghum Stover Residue With Ammonium Hydroxide on Cell Wall Composition and in vitro Digestibility

Abstract: The study was undertaken to determine the effects of ammonium hydroxide (NH 4 OH) treatment of sorghum stover residue on composition and in vitro dry matter disappearance (IVDMD) of two sorghum varieties, Dale (tall, sweet sorghum variety) and Brown mid rib (BMR) (Short, grain sorghum variety). The residue was treated with; water only (T00), 50 g NH 4 OH kg -1 residue dry matter (DM) (T50), 100 g NH 4 OH kg -1 DM (T100), and untreated control (neither water nor NH 4 OH) (TUN) and allowed to react for one week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
2
0
0
Order By: Relevance
“…However, in the Randolph variety, there was a decrease in the Solprot and an increase in ADIP as the level of NH 4 OH was increased from 50 to 100. Similar result was reported in a study with alkali treatment of sorghum stover (Yousuf et al, 2014).…”
Section: Protein Fractionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in the Randolph variety, there was a decrease in the Solprot and an increase in ADIP as the level of NH 4 OH was increased from 50 to 100. Similar result was reported in a study with alkali treatment of sorghum stover (Yousuf et al, 2014).…”
Section: Protein Fractionsupporting
confidence: 91%
“…Lack of treatment × variety interaction (Table 2) in mean CP of the residue from the two varieties (Randolph = 133 and Asmara = 135 g kg -1 DM) showed that CP content was not affected differently by the levels of NH 4 OH treatment. Similarly increased CP levels were observed in a study with sorghum stover residue treated with 50 and 100 g kg -1 DM of ammonium hydroxide (Yousuf et al, 2014). Similar effects of increased CP in poor quality forages as a result of ammoniation were also reported in wheat straw (Soleiman et al, 1979), Barley straw (Graham and Aman, 1984), limpograss (Brown et al, 1987), and tall fescue straw (Kallenbach et al, 2006).…”
Section: Protein Fractionsupporting
confidence: 64%